2018
DOI: 10.26714/mki.1.1.2018.1-11
|View full text |Cite
|
Sign up to set email alerts
|

Changes Of Symptoms And The Ability Of Anxiety Patients After Exercise Of Thought Stopping And Family Psychoeducation

Abstract: Patients with degenerative disease were hospitalized may experience an anxiety psychological problem affecting the condition of the illness. The handling of this case aims to determine the change of symptom signs and ability of anxiety patients after exercise thought stopping and family psychoeducation. The design was case study with 25 participants. The analysis was performed on symptoms and abilities of patients and families before and after nursing intervention, thought stopping and family psychoeducation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Some studies showed that thought stopping therapy increased the ability to control negative thoughts and effectively overcome anxiety (13)(14)(15)(16)(17)(18). Thought stopping combined with family psychoeducation can also reduce anxiety due to degenerative diseases (19).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that thought stopping therapy increased the ability to control negative thoughts and effectively overcome anxiety (13)(14)(15)(16)(17)(18). Thought stopping combined with family psychoeducation can also reduce anxiety due to degenerative diseases (19).…”
Section: Discussionmentioning
confidence: 99%